Reversing Early Stage Prostate Cancer in a Hypertensive Patient: A Case Study on Nutritional Cum Phyto-Therapy - Yap, Steve (International Journal of Biotechnology for Wellness Industries, 2012)
While prostate cancer is the most common male malignancy in the West, it is ranked as the number two cancer death for non-smokers in many developing countries. This case study demonstrates how an early stage prostate cancer might be treated by a comprehensive and evidence-based nutritional cum phytotherapy if patient is given the option of using it. According to the ANMP (www.anmp.org.my), a nutritional therapy is used to treat, control, or prevent chronic disorders by impacting on the hormonal, neurological, and immune functions of the patient. It may take a decade or longer to develop a malignancy. Three quarter of prostate cancer occurs in men over fifty five years when they go through andropause, which is evidenced partly by elevation in their oestrogen levels. However, being overweight or obese may trigger early progression of prostate cancer in men.